Oxidative conversion of glucose to gluconic acid by iron(iii) chloride in water under mild conditions. Issue 8 (26th January 2016) - Zhang, Hongdan; Li, Ning; Pan, Xuejun; Wu, Shubin; Xie, Jun
Abstract : A simple method to oxidize glucose into gluconic acid in a concentrated FeCl3 solution under mild conditions was developed. Abstract : A simple method was demonstrated to oxidize glucose into gluconic acid in a concentrated FeCl3 solution. The maximum gluconic acid yield (52.3%) was achieved in the 40% FeCl3 solution at 110 °C in 4 hours. Formic and acetic acids were the main coproducts with an yield of 10–20%.